A 48, XXXX female. Issue 2 (June 1974) - Peña, S. D. J.; Ray, M.; Douglas, G.; Loadman, E.; Hamerton, J. L.
Abstract : A four-year-old mildly retarded girl with a 48, XXXX karyotype is described. Her phenotype is compared to previously reported cases.